Legal philosophy and theories of legal interpretation (selected problems) - Zirk-Sadowski, Marek; Bekrycht, Tomasz (Acta Universitatis Lodziensis. Folia Iuridica, 2017)
The content of the article briefly presents the issues connected with theories of legal interpretation. The authors point to two methodological attitudes towards cognizing legal interpretation. They result in descriptive and prescriptive theories of legal interpretation and indicate creating a notion of ‘theory-concept’ in legal interpretation. The authors mark three groups of such theory-concepts in Polish legal theory.